2001
DOI: 10.1021/ma001836p
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photophysics of α-Hydroxy Ketones

Abstract: Time-resolved laser flash spectroscopy with transient detection by time-resolved UV−vis, IR, and EPR has been employed to investigate the photochemistry and photophysics of a series of derivatives of 2-hydroxy-2-methyl-1-phenyl propanone, a model photoinitiator for free radical polymerization. H, Cl, and F substituents at the para position promote the n,π* nature of the lowest triplet state and favor fast and efficient α-cleavage from T1 upon irradiation. In contrast, dimethylamino and thioether substitution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
162
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 28 publications
10
162
0
1
Order By: Relevance
“…The photochemistry of α-hydroxy ketones has been well characterized and the homolytic rupture of the α-cleavage bond favored by alkylation of the 2-hydroxy group occurs in the picosecond time scale after excitation [62]. The case of I-2959 is remarkable since is commercially available, water-soluble, and produces ketyl radicals with a quantum yield of 0.29 in fast photocleavage from a triplet state with a lifetime of just 11 ns [62].…”
Section: Photochemical Methodsmentioning
confidence: 99%
“…The photochemistry of α-hydroxy ketones has been well characterized and the homolytic rupture of the α-cleavage bond favored by alkylation of the 2-hydroxy group occurs in the picosecond time scale after excitation [62]. The case of I-2959 is remarkable since is commercially available, water-soluble, and produces ketyl radicals with a quantum yield of 0.29 in fast photocleavage from a triplet state with a lifetime of just 11 ns [62].…”
Section: Photochemical Methodsmentioning
confidence: 99%
“…[11][12][13] When 1 is covalently bound to PMA, an analogous photochemical primary process is expected except that the resultant benzoyl radical must be attached to the PMA backbone, while the ketyl radical is free to diffuse away. In this study we have observed and investigated the transient polarized ESR signal of the ketyl radical as a function of pH.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, T 1 states revealing a 3 (np*) character are known to be more efficient concerning radical formation than 3 (pp*) states. 34 Since orbital analyses of the T 1 states of the three investigated initiator molecules differ insignicantly from each other (all photoinitiators show at least partly the 3 (np*) character), the observed differences in radical generation seem to have other origins. Regarding internal rotation effects [35][36][37] (rotation around the C(O)-C(OH) and C(O)-C(Me) 2 bond, respectively) the transient data do not allow for an analysis with respect to different conformers.…”
mentioning
confidence: 98%